2013
DOI: 10.1007/s00296-012-2643-6
|View full text |Cite
|
Sign up to set email alerts
|

Burden of systemic lupus erythematosus in Taiwan: a population-based survey

Abstract: This population-based study aimed to determine the trend of incidence, prevalence, and mortality of systemic lupus erythematosus (SLE) in a 6-year period in Taiwan. Patients with international classification of diseases ninth revision (ICD-9) code 710.0 were retrieved from the Taiwanese National Health Insurance Research Database (NHIRD), which covered more than 96 % of the entire population, and from the Ministry of Interior between 2003 and 2008 in Taiwan. Patients with SLE registered as catastrophic illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 18 publications
8
36
1
Order By: Relevance
“…A recent large hospital‐based study in the UK showed significant association between SLE and sarcoidosis (aOR, 8.33; 95% CI, 2.71–19.4) . In our study, the prevalence of SLE in the control group was consistent with a previous nationwide survey in Taiwan, which suggested that the matched control group we sampled could represent the population. Our analysis showed that sarcoidosis patients could have been likely to develop SLE (aOR, 2.98), but the small case number rendered the statistical evaluation insignificant.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A recent large hospital‐based study in the UK showed significant association between SLE and sarcoidosis (aOR, 8.33; 95% CI, 2.71–19.4) . In our study, the prevalence of SLE in the control group was consistent with a previous nationwide survey in Taiwan, which suggested that the matched control group we sampled could represent the population. Our analysis showed that sarcoidosis patients could have been likely to develop SLE (aOR, 2.98), but the small case number rendered the statistical evaluation insignificant.…”
Section: Discussionsupporting
confidence: 90%
“…The remaining two diseases, SLE and psoriasis, were not uncommon in Taiwan with prevalence of 97.5 and 278.3 per 100 000 population, respectively . There are increasing reports supporting the coexistence of SLE and sarcoidosis with approximately 30 cases reported in the English‐language published work, including four Asian cases .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NHIRD has been described in-depth in our previous studies [6, 2126]. In short, Taiwan National Health Insurance (NHI) program commenced on 1 March 1995.…”
Section: Methodsmentioning
confidence: 99%
“…With early diagnosis and enhanced treatment strategies, the survival of patients with systemic lupus erythematosus (SLE) has improved dramatically in the last 50 years (Doria, Gatto, Zen, Iaccarino, & Punzi, ). However, China, the largest country in the Asia‐Pacific area, has a relatively higher prevalence rate than other countries (Mok, ; Yeh, Yu, Chan, Horng, & Huang, ), and lupus nephritis (LN) is still the most frequent visceral complication of SLE, accounting for increased morbidity (including end‐stage renal disease) and mortality rates (Mok, ). Above all, it is important to explore the mechanism of LN and identify personalized treatment options.…”
Section: Introductionmentioning
confidence: 99%